2018
DOI: 10.1038/nrdp.2018.29
|View full text |Cite
|
Sign up to set email alerts
|

Borderline personality disorder

Abstract: Caretakers are often intimidated or alienated by patients with borderline personality disorder (BPD), compounding the clinical challenges posed by the severe morbidity, high social costs and substantial prevalence of this disorder in many health-care settings. BPD is found in ∼1.7% of the general population but in 15-28% of patients in psychiatric clinics or hospitals and in a large proportion of individuals seeking help for psychological problems in general health facilities. BPD is characterized by extreme s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
340
0
32

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(380 citation statements)
references
References 232 publications
8
340
0
32
Order By: Relevance
“…Additionally, the authors found a small but significant correlation between illusory body ownership and state and trait dissociation after controlling for BPD symptom severity. We extend these findings by (1) testing group differences in the relative endorsement of target vs. non-target items, (2) probing responses to individual target items to explore more granular group differences in illusory experience, (3) directly testing hypotheses about asynchronous stimulation, and (4) exploring relationships between illusory body ownership and BPD symptom phenotypes and dimensional measures of maladaptive personality.…”
Section: The Current Study: Probing Body Plasticity In Bpdmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, the authors found a small but significant correlation between illusory body ownership and state and trait dissociation after controlling for BPD symptom severity. We extend these findings by (1) testing group differences in the relative endorsement of target vs. non-target items, (2) probing responses to individual target items to explore more granular group differences in illusory experience, (3) directly testing hypotheses about asynchronous stimulation, and (4) exploring relationships between illusory body ownership and BPD symptom phenotypes and dimensional measures of maladaptive personality.…”
Section: The Current Study: Probing Body Plasticity In Bpdmentioning
confidence: 95%
“…The embodied self in Borderline Personality Disorder 1.1.1. Self-disturbance is a core feature of BPD Aberrations of self-experience and identity are considered a core symptoms of Borderline Personality Disorder (BPD) [1]. Self-disturbance is characterized by a markedly persistent unstable sense of self that can be realized by dramatic shifts in self-image, shifting goals and values, and feelings of emptiness, dissociation, and non-existence [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of BPD in adolescents is similar to that found in adult populations: 1–3% in the general population, between 11–22% in outpatients, and up to 33–49% in inpatient settings (Sharp & Wall, ). BPD typically onsets in adolescence, and genetic, neurobiological, and psychosocial factors are thought to be central to its etiology (Gunderson, Herpertz, Skodol, Torgersen, & Zanarini, ; Thomsen, Ruocco, Carcone, Mathiesen, & Simonsen, ; Winsper et al, ). The reliability and validity of the BPD diagnosis in adolescence resemble that of adults, and BPD symptoms in childhood or adolescence are predictive of later functional disability (Grant et al, ; Sharp, ; Winsper et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Borderline personality disorder (BPD) is a psychiatric condition characterized by instability of interpersonal relationships, self‐image, and affect and marked impulsivity . BPD is associated with severe functional impairment and substantial mortality rate . A community prevalence of BPD is approximately 0.4–1.8% .…”
Section: Introductionmentioning
confidence: 99%